ESTIMASI NILAI LINGKUNGAN PERKEBUNAN KELAPA SAWIT DITINJAU DARI NERACA AIR TANAMAN KELAPA SAWIT (STUDI KASUS: PERKEBUNAN KELAPA SAWIT DI KECAMATAN DAYUN, KABUPATEN SIAK, PROPINSI RIAU)THE ESTIMATION OF OIL PALM PLANTATION ... - Isa Teguh Widodo; Bambang Dwi Dasanto (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2010)
Dayun area is one of the centers of oil palm plantation in Siak Regency. State-owned company that develops oil palm plantation in Dayun is PT Perkebunan Nusantara V (PTPN V) which is the first company developing oil palm plantation in Siak Regency. The oil palm plantations cause various effects to the environment; one of them is the decreasing water availability for the water stakeholders. The decreasing water availability causes additional cost to the community. The objectives of this study were to determine the decreasing of water availability which was caused by oil palm plantation, and its cost to meet the needs of water. The study used water balance model by Thornwhite 1957 and Willingness to Pays (WTP) analysis using questionaire of Contingent Valuation Method (CVM) in Sawit Permai, Dayun Subdistrict, Siak Regency. The land cover, before and after, affects the water balance which impacts the water availability in Dayun. The decreasing water availability was comparable with the increasing water demand in oil palm plantation, equal to 67 mm/year. Oil palm plantation had greater runoff than that of forest. The need of water in oil palm plantation in Dayun was 42.728 liters/ha/day, with the daily need of a single palm tree equal to 0,012 m3/s. Based on the analysis of debt estimation, there is debt decreasing which indicates the decreasing water availability in Dayun, around 349 m3/s yearly. The estimated value of the environment for oil palm plantation by water resources consumption based on the difference of forest and oil palm plantation during the dry season (JJA) is equal to Rp 7.500.000. Average WTP for the water conservation program is Rp 26.400, with WTP maximum and minimum up to Rp 45.000 and Rp 5.000, respectively. The economic value of water conservation program is Rp 18.850.000/month.Dayun area is one of the centers of oil palm plantation in Siak Regency. State-owned company that develops oil palm plantation in Dayun is PT Perkebunan Nusantara V (PTPN V) which is the first company developing oil palm plantation in Siak Regency. The oil palm plantations cause various effects to the environment; one of them is the decreasing water availability for the water stakeholders. The decreasing water availability causes additional cost to the community. The objectives of this study were to determine the decreasing of water availability which was caused by oil palm plantation, and its cost to meet the needs of water. The study used water balance model by Thornwhite 1957 and Willingness to Pays (WTP) analysis using questionaire of Contingent Valuation Method (CVM) in Sawit Permai, Dayun Subdistrict, Siak Regency. The land cover, before and after, affects the water balance which impacts the water availability in Dayun. The decreasing water availability was comparable with the increasing water demand in oil palm plantation, equal to 67 mm/year. Oil palm plantation had greater runoff than that of forest. The need of water in oil palm plantation in Dayun was 42.728 liters/ha/day, with the daily need of a single palm tree equal to 0,012 m3/s. Based on the analysis of debt estimation, there is debt decreasing which indicates the decreasing water availability in Dayun, around 349 m3/s yearly. The estimated value of the environment for oil palm plantation by water resources consumption based on the difference of forest and oil palm plantation during the dry season (JJA) is equal to Rp 7.500.000. Average WTP for the water conservation program is Rp 26.400, with WTP maximum and minimum up to Rp 45.000 and Rp 5.000, respectively. The economic value of water conservation program is Rp 18.850.000/month.